2005
DOI: 10.1111/j.1474-8673.2004.00334.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotoxicity of digitalis glycosides: roles of autonomic pathways, autacoids and ion channels

Abstract: 1 Cardiac glycosides have been used for centuries as therapeutic agents for the treatment of heart diseases. In patients with heart failure, digoxin and the other glycosides exert their positive inotropic effect by inhibiting Na(+)-K(+)-ATPase, thereby increasing intracellular sodium, which, in turn, inhibits the Na(+)/Ca(2+) exchanger and increases intracellular calcium levels. As the therapeutic index of digitalis is narrow, arrhythmias are common problems in clinical practice. The mechanisms and mediators o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 119 publications
0
24
0
Order By: Relevance
“…Na ϩ -K ϩ -ATPase activity importantly regulates intracellular [Na ϩ ]. Na ϩ -K ϩ -ATPase inhibition, e.g., by cardiac glycosides, increases intracellular [Na ϩ ] and thereby inhibits Ca 2ϩ efflux via the NCX, which is a well established mechanism for increasing SR Ca 2ϩ content and cardiac contractility (Demiryü rek and Demiryü rek, 2005). Previous work has demonstrated that micromolar EGCG inhibits Na ϩ -K ϩ -ATPase activity in human red blood cell membranes (Rizvi , 2005).…”
Section: Nanomolar Egcg Enhances Myocyte Contractility Camentioning
confidence: 99%
“…Na ϩ -K ϩ -ATPase activity importantly regulates intracellular [Na ϩ ]. Na ϩ -K ϩ -ATPase inhibition, e.g., by cardiac glycosides, increases intracellular [Na ϩ ] and thereby inhibits Ca 2ϩ efflux via the NCX, which is a well established mechanism for increasing SR Ca 2ϩ content and cardiac contractility (Demiryü rek and Demiryü rek, 2005). Previous work has demonstrated that micromolar EGCG inhibits Na ϩ -K ϩ -ATPase activity in human red blood cell membranes (Rizvi , 2005).…”
Section: Nanomolar Egcg Enhances Myocyte Contractility Camentioning
confidence: 99%
“…Therefore, we attempted to define hypokalemia and/or hypokalemia disturbances as particular disturbances related to NO-system and possible therapeutic value of NOsystem-related agents: NO-synthase (NOS)-blocker, L-NAME, NOSsubstrate, L-arginine, and, particularly, stable gastric pentadecapeptide BPC 157 [4][5][6]. In this, we focused on so far not demonstrated with L-NAME/L-arginine application [1,2] NO-system-relations in mortal furosemide-diuresis-hypokalemia course; -ECG changes, carefully analyzed in rats [7] (prolongation of P, R, S, T waves and PR, RR, QRS, QT interval duration, and reduced amplitude of R, S, T wave (although not completely related to hypokalemia) [7]); -arrhythmias (AV conduction block, ventricular premature beats, ventricular tachycardia); -skeletal muscle myoclonus [8]; and -lethality 90-150 min post-furosemide. Likely, this furosemide-hypokalemia-NO-systemsyndrome should be worsened by L-NAME, ameliorated by L-arginine and finally, counteracted by BPC 157.…”
Section: Introductionmentioning
confidence: 99%
“…NO-system is proposed as endogenous cardioprotectant and antifibrillatory factor [1,2]. Diuretic-hypokalemia is an increasingly common cause of arrhythmias [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations